Generic Moves in The Literature Review Section of PhD Dissertations - Anjum , Muhammad Tahir; Masroor, Farzana (Pakistan Journal of Humanities and Social Sciences, 2023)
The dissertation/thesis as an academic genre has evolved in academic circles in the past 30 years or so. Research into various aspects of the academic genres in general and thesis writing, in particular, started more than two decades ago. However, not much research has been carried out regarding the theorizing of literature review writing as a separate genre in theses, especially in non-native English contexts. The present study aimed to fill the theoretical voids in the research area of Literature Review (LR) section in thesis writing in Pakistani academic settings; thus this study probes into the process of construction of literature reviewing to find out that how students organise this section and deal with the potential problems as an analytical piece of writing with sound argumentation. The current study has investigated the schematic patterns in the literature review through the framework of move analysis in genre theory. The data was drawn from fifteen (15) doctoral theses in the field of English linguistics. The methodology allows for an in-depth coding of the LR chapters in theses to investigate the rhetorical organization. In the coding process, the study has also taken insights from the two previous models of Kwan (2006) and Swales’ seminal CARS model (1990) in order to study the moves (and steps) as rhetorical units. The results of the study reflect the dominant presence of Move 1, Move 2 and Move 4, whereas the employment of Move 3 is comparatively less which justifies the worth of writer’s work. This reveals that the students resort to these moves more often to perform a ritual of literature reviewing and in dire need to be trained enough to craft the LRs argumentatively. Thus, researchers have proposed a revised model to overcome the shortcoming.